Intraseasonal variability and eddy-induced structural modulation of the North Pacific intermediate water revealed by multi-mooring observations - Qiang Ren; Yansong Liu; Yansheng Zhang; Shumin Tu; Wei Huang; Feng Nan; Ran Wang; Xinyuan Diao; Jianfeng Wang; Xinchuang Liu; Zifei Chen; Fei Yu (Ocean Science, 2026)
The North Pacific Intermediate Water (NPIW) plays an important role in regulating thermohaline structure and biogeochemical distributions in the North Pacific. However, limited continuous observations have hindered our understanding of its short-term variability and structural response to mesoscale processes. Based on 1 year mooring observations from three sites (M1–M3) in the western North Pacific, this study investigates the intraseasonal structural variability of the NPIW and its modulation by mesoscale eddies. The NPIW thickness exhibits pronounced intraseasonal variability, with a dominant period of approximately 60–80 d that is coherent among the three mooring sites. Unlike previous studies that mainly focused on temperature and salinity anomalies, this study introduces NPIW thickness as a structural diagnostic parameter to characterize the vertical compression and expansion of the intermediate layer associated with mesoscale variability. The results reveal a clear inverse relationship between NPIW thickness and salinity, indicating that anticyclonic conditions are generally associated with thinner and more saline intermediate layers, whereas cyclonic conditions correspond to thicker and relatively fresher layers. Spatial composite analyses further show that thickness and salinity responses exhibit clear regional differences, with stronger variability near the western boundary, likely related to complex water-mass redistribution and possible mixing processes. These findings provide quantitative observational evidence for intraseasonal variability in NPIW thickness and highlight its usefulness as a diagnostic indicator for mesoscale–intermediate water interactions in the North Pacific.